Conjunctival effects of canine distemper virus-induced keratoconjunctivitis sicca - de Almeida, Denize E.; Roveratti, Cristina [UNESP]; Brito, Fabio L. C.; Godoy, Guilherme S.; Duque, Juan C. M.; Bechara, Gervasio Henrique [UNESP]; Laus, Jose L. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
ObjectiveThis study compared the histopathology of canine distemper virus (CDV)-induced keratoconjunctivitis sicca (KCS) to non-infectious KCS in conjunctival tissues.Animals studiedForty mongrel dogs were assigned to three distinct groups: (i) non-infectious KCS (G1, n = 10), (ii) CDV-induced KCS (G2, n = 20), and (iii) healthy animals without any ocular alterations (G3, n = 10).ProcedureIgG titers and physical and ophthalmic examinations (e.g. Schirmer tear test [STT], tonometry, biomicroscopy, indirect biomicroscopy, and fluorescein test) were performed on all dogs. Conjunctival biopsies were collected and examined microscopically.ResultsNon-infectious and CDV-induced KCS demonstrated similar histopathological changes. Both types of KCS correlated with low STT, conjunctival hyperemia, mucopurulent ocular discharge, predominant lymphoplasmacytic infiltration, and acantholysis and keratinization of the ocular surface. G1 had lower conjunctival goblet cell counts than G3. Inclusion bodies were sporadically found in conjunctival samples of dogs from G2. The severity of ocular lesions in G1 and G2 did not correlate with the histopathological findings.ConclusionsDogs with non-infectious and CDV-induced KCS had very similar conjunctival histopathology. Our findings suggest that the pathophysiology of CDV-induced KCS is likely to be the same as non-infectious KCS, that is, a result of lacrimal deficiency and inflammation of the ocular surface.
Keywords: conjunctivae; distemper; Dog; Inflammation; keratoconjunctivitis sicca; morbillivirus